Shock Index and Early Recognition of Sepsis in the Emergency Department: Pilot Study - Berger, Tony; Green, Jeffrey; Horeczko, Timothy; Hagar, Yolanda; Garg, Nidhi; Suarez, Alison; Panacek, Edward; Shapiro, Nathan (The western journal of emergency medicine, 2013)
Screening for severe sepsis in adult emergency department (ED) patients may involve potential delays while waiting for laboratory testing, leading to postponed identification or over-utilization of resources. The systemic inflammatory response syndrome (SIRS) criteria are inaccurate at predicting clinical outcomes in sepsis. Shock index (SI), defined as heart rate / systolic blood pressure, has previously been shown to identify high risk septic patients. Our objective was to compare the ability of SI, individual vital signs, and the systemic inflammatory response syndrome (SIRS) criteria to predict the primary outcome of hyperlactatemia (serum lactate ≥ 4.0 mmol/L) as a surrogate for disease severity, and the secondary outcome of 28-day mortality. We performed a retrospective analysis of a cohort of adult ED patients at an academic community trauma center with 95,000 annual visits, from February 1st, 2007 to May 28th, 2008. Adult patients presenting to the ED with a suspected infection were screened for severe sepsis using a standardized institutional electronic order set, which included triage vital signs, basic laboratory tests and an initial serum lactate level. Test characteristics were calculated for two outcomes: hyperlactatemia (marker for morbidity) and 28-day mortality. We considered the following covariates in our analysis: heart rate >90 beats/min; mean arterial pressure < 65 mmHg; respiratory rate > 20 breaths/min; ≥ 2 SIRS with vital signs only; ≥2 SIRS including white blood cell count; SI ≥ 0.7; and SI ≥ 1.0. We report sensitivities, specificities, and positive and negative predictive values for the primary and secondary outcomes. 2524 patients (89.4%) had complete records and were included in the analysis. 290 (11.5%) patients presented with hyperlactatemia and 361 (14%) patients died within 28 days. Subjects with an abnormal SI of 0.7 or greater (15.8%) were three times more likely to present with hyperlactatemia than those with a normal SI (4.9%). The negative predictive value (NPV) of a SI ≥ 0.7 was 95%, identical to the NPV of SIRS. In this cohort, SI ≥ 0.7 performed as well as SIRS in NPV and was the most sensitive screening test for hyperlactatemia and 28-day mortality. SI ≥ 1.0 was the most specific predictor of both outcomes. Future research should focus on multi-site validation, with implications for early identification of at-risk patients and resource utilization.